Wrong pedogenetic assumptions: a case study of the soils developed over talc in Southern Guinea Savanna of Nigeria using clay mineralogy. Issue 1 (1st January 2018) - Ajiboye, Godwin A; Ogunwale, JA; Talbot, James; Mesele, Samuel A
Abstract : It is often assumed that ultrabasic parent material leads to the formation of soils rich in 2:1 clays and dibasic cations. However, in a tropical environment with intense weathering, this assumption may not be true. To investigate this assumption soil samples taken from representative profiles of six mapping units developed over talc (an utrabasic parent material) were subjected to particle size analysis, analysis of the weathering ratios of Fe and Al, clay fractionation and X-ray diffraction (XRD). Results showed that the underlying rock consisted of talc admixed with chlorite and kaolinite. The dominant clay minerals of the soils were kaolinite and mica. One profile (EJ4) with imperfect drainage had noticeable quantities of smectite in the A and C horizons and a minor quantity of smectite in the B horizon. The soils were highly weathered and the silt:silt + clay and Feo :Fed ratios were suitable indices of stage of soil development. The XRD patterns of the weathered and unweathered underlying rocks apparently showed a complete weathering out of the talc material, to be replaced by variable quantities of kaolinite, smectite and illite. These observations negate the assumption, especially in a tropical environment. The studied soils may not have been truly residual as presumed but could have indeed received additional inputs.